Legal Basis for Introducing Restrictions on Human Rights and Freedoms during the First Wave of the COVID-19 Pandemic - Dobrzeniecki, Karol; Przywora, Bogusław (Review of European and Comparative Law, 2021)
In this article, we attempt to present the legal grounds for introducing restrictions on human rights during the COVID-19 pandemic from a comparative legal perspective. We refer to the findings of a research project completed in 2020, trying to synthesize them and confront them with existing theoretical models. We strive to capture general patterns in the legal basis for states’ actions in response to global threats such as the COVID-19 pandemic. Comparative legal research contributes to the creation of universal solutions, which, taking into account the specificity of the system, can then be applied in local conditions.